Outsourcing spare part inventory management in the paper industry : a case study on Edet paper mill - Skärberg, Erik (SLU/Dept. of Forest Economics, 2019)
The paper industry is a large-scale processing industry where a continuous production, around the clock is necessary This means that it is necessary to carry an inventory of spare parts. This however comes with costs in the form of mainly cost of capital and handing costs. Inventory management is about balancing the cost of keeping inventory and the service level to the production. This study explores the possibilities of outsourcing the spare part inventory management at a paper mill. The study is a case study that uses a mixed-method approach. The study finds that by outsourcing the spare part sourcing and inventory control to a third-party logistics provider (3PLP) potential cost savings can be reached primarily by a more streamlined re-stocking process and taking advantage of specialization, aggregation and economics of scale. The major motive behind outsourcing is saving costs and making sure that the company can focus on value-adding activities and its core-compentence. The items that are best suitable for an outsourcing solution is generic low-value items such as Tools, Utensils and Bearings.